2012
DOI: 10.1002/hed.23052
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco, alcohol, body mass index, physical activity, and the risk of head and neck cancer in the prostate, lung, colorectal, and ovarian (PLCO) cohort

Abstract: Cigarette smoking is clearly the most important head and neck cancer risk factor in this population. The reduced cancer risk due to physical activity was consistent with results from a pooled analysis of case-control studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 28 publications
6
65
3
2
Order By: Relevance
“…In a study carried out in Brazil to estimate the PAF of modifiable risk factors for 25 types of cancer, it was observed that highest PAF was related to smoking, followed by infections, low intake of fruits and vegetables, lack of physical activities, overweight and obesity 19 . The differences in HNC fractions attributable to tobacco and alcohol found in this study are similar to those observed for Latin America 5 , however, higher than the ones detected in other regions of the world 10,23,[27][28][29] , and may be the expression of local patterns and habits of tobacco and alcohol consumption in the cities analyzed in the Center-West, Southeast and South regions. There is great variation in the occurrence of HNC in the world 30,31 .…”
Section: Discussionsupporting
confidence: 82%
“…In a study carried out in Brazil to estimate the PAF of modifiable risk factors for 25 types of cancer, it was observed that highest PAF was related to smoking, followed by infections, low intake of fruits and vegetables, lack of physical activities, overweight and obesity 19 . The differences in HNC fractions attributable to tobacco and alcohol found in this study are similar to those observed for Latin America 5 , however, higher than the ones detected in other regions of the world 10,23,[27][28][29] , and may be the expression of local patterns and habits of tobacco and alcohol consumption in the cities analyzed in the Center-West, Southeast and South regions. There is great variation in the occurrence of HNC in the world 30,31 .…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies reported that the occurrence of OC is associated with alcohol consumption (2,3), smoking (3,4), betel nut chewing (5), and human papilloma virus infection (6). Despite improved clinical interventions, including surgery, radiotherapy, chemotherapy and chemo-radiotherapy, the 5-year survival rate for patients with OC has remained poor over the previous several decades (7).…”
Section: Introductionmentioning
confidence: 99%
“…Por esse motivo, projetos de prevenção e tratamento vêm sendo implantados para melhorar a saúde pública. Estudos relacionam a prevenção e controle do câncer à mudança de estilo de vida, como, por exemplo, redução do tabagismo, alimentação com redução de produtos de origem animal e aumento no consumo de frutas e vegetais, além da recomendação para a realização de atividade física 4,5 . Nesse contexto, a fisioterapia é indicada para assistência e promoção da saúde, essencial para manutenção e melhora da qualidade de vida.…”
Section: Perfil Clínico Dos Pacientes Atendidos Em Um Ambulatório De unclassified